Impact of submerged vegetation, water flow field and season changes on sediment phosphorus distribution in a typical subtropical shallow urban lake: Water nutrients state determines its retention and release mechanism. Issue 3 (June 2022) - Bai, Guoliang; Xu, Dong; Zou, Yilingyun; Liu, Yunli; Liu, Zisen; Luo, Feng; Wang, Chuan; Zhang, Cong; Liu, Biyun; Zhou, Qiaohong; He, Feng; Wu, Zhenbin; et al.
Abstract: Sediment phosphorus act as a vital role on eutrophication in shallow lakes. The knowledge about the effect of submerged vegetation types and water flow field on sediment total phosphorus (STP) and the relationship with environmental variables in eutrophic shallow lakes is limited. In this study, temporal and spatial characteristics of water and sediment nutrients in a typical subtropical shallow urban lake Hangzhou West Lake were evaluated, meanwhile, quantitative analyses were investigated to determine the contribution of water nutrients, sediment properties and submerged vegetation on retention and release of sediment total phosphorus. Results illustrated that the water nutrients characteristics are determined by the water flow field and season changes. Additionally, much lower Nitrogen/Phosphorus (N/P) ratio (6.29 ± 3.25–16.82 ± 1.54) of downstream locations compared to that (9.79 ± 1.30–26.33 ± 2.90)of upstream and midstream locations in lake water, which led to the inconsistent characteristics between water nutrients and water chlorophyll a (Chl-a) and trophic state index (TSI). Temporal and spatial distribution of STP determined by season changes, water flow field types, submerged vegetation types, and deposition of aluminium salt (Al-salts) originated from water diversion project. The effect of interception of submerged vegetation and flow velocities reduction induced by water flow field types changed are similar that both accelerate the phosphorus retention in sediments. Results of structural equation modeling illustrated that the main effect on STP is water nutrients including water total nitrogen (TN), Chl-a, and TSI, which implied that the nitrogen limitation is the key factor. Water nutrients significantly and directly affect (coefficient is 0.254) STP while submerged vegetation exhibited indirectly effect induced by water nutrients (coefficient is 0.077) and sediment properties (coefficient is 0.062). The loss of nitrogen and an increase in phosphorus mainly influence the submerged vegetation distribution, higher trophic level index and sediment phosphorus release. Graphical Abstract: ga1 Highlights: Temporal and spatial characteristics of water and sediment nutrients were evaluated. Quantitative analysis contribution on sediment total phosphorus were investigated. Structural equation model shows water nutrients governs sediment total phosphorus. Submerged vegetation exhibited indirectly effect on sediment total phosphorus. Decreased submerged vegetation distribution is due to lower N:P ratio.